The Impact of Social Media on Students' Awareness and Engagement with Social Issues - , Disha Agarwal; , Govind Singh Kushwaha; , Basu Anand; , Ishita Mishra; , Komal Sharma (Archives of Current Research International, 2024)
Aims: This study aimed to investigate the impact of social media on university students' awareness and engagement with social issues. Study Design: The study followed a cross-sectional study design. Place and Duration of Study: The study was conducted at G B Pant University of Agriculture and Technology, Pantnagar, Uttarakhand, India, over a period of three months from March 2024 to June 2024. Methodology: A convenience sampling technique was used to select 100 students, predominantly male (74.00%), mostly aged 18-24 years (56.00%), with the majority from the College of Agriculture (75.00%). Data were collected using a structured Google form survey assessing social media usage, awareness of social issues, and engagement behaviors. Descriptive statistics were used to analyze the data. Results: The study found that social media significantly enhances awareness of social issues, with (54.00%) of respondents rating their awareness as high after exposure, compared to (31.00%) before social media exposure. Engagement levels were moderate, with (58.00%) of students participating in online campaigns and (46.00%) moderately likely to engage in social issues after exposure. Key actions taken included sharing posts (53.00%), volunteering (45.00%), attending events and donating (42.00%), and using hashtags (33.00%). Conclusion: The results demonstrate that social media is a powerful tool for enhancing awareness and encouraging civic engagement among university students, suggesting its potential for driving meaningful social change.